Super Bowl Advertising Effectiveness : Is There a Return on Investment Based on Stock Market Data. - Huegel, Justin; Rozumalski, Dan (My University, 2009)
This study examines whether advertisers in the 1996-2008 Super Bowls experienced a stock price gain relative to the more broad-based S&P 500 market performance for the week immediately before and after the game. The study also examines whether a significant difference exists between the daily stock price changes of Super Bowl stocks relative to the S&P 500 market performance over the ten trading days bracketing the event.
Color poster with text and graphs describing research conducted by Justin Huegel and Dan Rozumalski, advised by Charles L. Tomkovick and Rama Yelkur.
Keywords: Super Bowl--Economic aspects; Television advertising--Evaluation; Stocks--Prices--Research; Posters